DTC Torque Ripple Minimization Based on PSO-PID Controller - Rashag, Hassan Farhan; S. P., Koh; Abdalla, Ahmed N.; Nadia M. L., Tan; K. H., Chong; S. K., Tiong (Academic Journals, 2012)
In conventional direct torque controlled (DTC) induction motor drive, there is usually undesired torque and flux ripple. The given torque is the speed output regulator; therefore, it necessarily continues tuning for adjusting parameters Kp, Ki. In conventional proportional- integral (PI) speed controller, the performance of motor may differ over time that may cause unexpected torque disturbances, causing sluggishness of a control system. Tuning PID parameters are essential to DTC system to improve the performance of the system at a low speeds. In this paper particle swarm optimization (PSO) proposed to correct the parameters (Kp, Ki) of a speed controller in order to minimize torque ripple, flux ripple, and stator current distortion. Firstly, introduce brief description for conventional DTC design and PSO. Secondly, close loop speed controller in DTC for induction motor using PSO technique to provide high performance of accuracy. Finally, simulation results demonstrate that a reduction of torque and flux ripples is achieved in a whole speed range.